Design Architecture Influencer Social Media Management System Using Distributed Ledger Technology - Dannies Pahlevi; Gunawan Wang (Management Analysis Journal, 2023)
The social media industry is currently in hype. However, one thing that was born from this industry is the endorsement business. The background that started this research is because this business has the possibility of fraud on endorsements. The purpose of this research is to solve the problem of fraud by utilizing the architectural design of Distributed Ledger Technology. What is meant is a private blockchain called DLT or Distributed Ledger Technology. By using this technology there is a solution to make the endorsement business trusted and unchanged. With the advantages of blockchain nature, we can create trusted and immutable backing, especially if we implement private DLT. The conclusion we've come to is that in the last 4 years technologies have developed that enable APIs for DLT, what we're going to do is design an API layer that will communicate to the DLT network.